Ecoregional Site Study on Small Islands: A case study of the significance of flora for fisheries in the Anambas Islands - Budiman, Mokhamad Asyief Khasan; Winata, Bayu; Christian, Yoppie; Desmiwati, Desmiwati; Wardhana, Ari Gunawan (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2024)
The formation of the Anambas Islands was a form of earth's surface dynamics that occurred over millions of years. In the process, there were at least eight land formations on the Sunda shelf. This evolution of the earth's surface led to the emergence of large islands on the Sunda shelf along with small islands around them. This also makes the Sundanese shelf part of the volcano's volcanic route. The Bunguran Formation was a bedrock complex that is thought to originate from deep-sea sediments of the Jurassic-Cretaceous age. The rocks are quite old, indicating that this formation was exposed to the surface and formed islands in the arc of the Anambas Islands group. All of these natural processes create a unique type of ecosystem, namely a rocky beach ecosystem, where the rocks at the study location were large rocks with cliffs on some of the coastlines. Meanwhile, sloping and protected locations allow the dust substrate to mix with sand to create a thin mud that allows mangrove forests to grow. Development in Anambas was carried out to grow the economy in this region. The Regional Government consistently develops in various fields. Some that stand out are the fisheries, tourism, and oil and gas sectors. It was believed that forests play a role in maintaining fisheries stocks on the coast, especially mangrove forests. Because of this, there was a need for a study that could display the flora profile in the Anambas Islands ecoregion. The results of the study show 23 species of flora in coastal forests and seven species of mangroves.